PENERAPAN MEDIA LAGU DALAM MENGENALKAN JENIS-JENIS SUARA MANUSIA PADA PEMBELAJARAN SENI MUSIK KELAS 5 SEKOLAH DASAR - Ferdinal, Hanafa Putri; Handayani, Rela; Indah, Riska; Khairani, Rizka; Ardipal; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of song media in introducing the types of human voices in fifth-grade elementary school music learning. The research employed a qualitative descriptive approach involving one teacher and 15 fifth-grade students at SD Negeri 20 Kalumbuk, Kuranji District, Padang City. Data were collected through observations, interviews, documentation, and field notes during the learning process. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that the song media entitled “Kenali Suara Kita” (“Recognizing Our Voices”), combined with Canva-based visual media and a smartboard, supported active, meaningful, and enjoyable learning experiences. The use of songs helped students identify and differentiate types of human voices, such as soprano, alto, tenor, and bass, through listening, singing, discussion, worksheet completion, presentation of results, and interactive evaluation activities using Wordwall. Students’ responses indicated high levels of attention, active participation in learning, an improved understanding of the concept of human voice types, and positive enthusiasm throughout the learning activities. The findings suggest that song media can serve as an effective alternative instructional medium to help students understand the topic of human voice types in elementary school music education.